Black body radiation as a function of frequency and wavelength: an experimentally oriented approach - Ademir L. Xavier Jr.; Sergio Celaschi (Revista Brasileira de Ensino de Física, 2012)
It is well known that the peak of black body radiation depends on the adopted description, whether as a function of frequency or wavelength. This paper is a pedagogical exposition of how to write and estimate Planck's distribution spectrum on two distinct spectrograph scales. We show that the emitted power of the Black Body maximum is unique and does not coincide with the peak measured whether in frequency or wavelength. We then make a generalization with other distribution functions in order to further clarify the apparent issue.